Extracorporeal perfusion in vascularized composite allotransplantation: current concepts and future prospects - Kückelhaus, Maximilian; Puscz, Flemming; Dermietzel, Alexander; Dadras, Mehran; Fischer, Sebastian; Krezdorn, Nicco; Pomahac, Bohdan; Hirsch, Tobias (Annals of plastic surgery, 2018)
AbstractSevere injuries of the face and limbs remain a major challenge in today's reconstructive surgery. Vascularized composite allotransplantation (VCA) has emerged as a promising approach to restore these defects. Yet, there are major obstacles preventing VCA from broad clinical application. Two
Gesehen am 14.11.2019